Question and Answers Forum

All Questions      Topic List

Algebra Questions

Previous in All Question      Next in All Question      

Previous in Algebra      Next in Algebra      

Question Number 198919 by necx122 last updated on 25/Oct/23

Find the sum of the fourth powers of  the roots of equation:  7x^3 −21x^2 +9x+2=0

$${Find}\:{the}\:{sum}\:{of}\:{the}\:{fourth}\:{powers}\:{of} \\ $$$${the}\:{roots}\:{of}\:{equation}: \\ $$$$\mathrm{7}{x}^{\mathrm{3}} −\mathrm{21}{x}^{\mathrm{2}} +\mathrm{9}{x}+\mathrm{2}=\mathrm{0} \\ $$

Commented by necx122 last updated on 25/Oct/23

wow! Really learning new things. Thank you sir.

Answered by deleteduser1 last updated on 25/Oct/23

Let roots be a,b,c,. Then a+b+c=((−(−21))/7)=3  ab+bc+ca=(9/7);abc=((−2)/7)    a^4 +b^4 +c^4 =(a^2 +b^2 +c^2 )^2 −2[(ab)^2 +(bc)^2 +(ca)^2 ]  (a^2 +b^2 +c^2 )=(a+b+c)^2 −2(ab+bc+ca)=9−((18)/7)  =((63−18)/7)=((45)/7)  (ab)^2 +(bc)^2 +(ca)^2 =[ab+bc+ca]^2 −2abc(a+b+c)  =((81)/(49))+((84)/(49))=((165)/(49))  ⇒a^4 +b^4 +c^4 =(((45)/7))^2 −((330)/(49))=((1695)/(49))

$${Let}\:{roots}\:{be}\:{a},{b},{c},.\:{Then}\:{a}+{b}+{c}=\frac{−\left(−\mathrm{21}\right)}{\mathrm{7}}=\mathrm{3} \\ $$$${ab}+{bc}+{ca}=\frac{\mathrm{9}}{\mathrm{7}};{abc}=\frac{−\mathrm{2}}{\mathrm{7}} \\ $$$$ \\ $$$${a}^{\mathrm{4}} +{b}^{\mathrm{4}} +{c}^{\mathrm{4}} =\left({a}^{\mathrm{2}} +{b}^{\mathrm{2}} +{c}^{\mathrm{2}} \right)^{\mathrm{2}} −\mathrm{2}\left[\left({ab}\right)^{\mathrm{2}} +\left({bc}\right)^{\mathrm{2}} +\left({ca}\right)^{\mathrm{2}} \right] \\ $$$$\left({a}^{\mathrm{2}} +{b}^{\mathrm{2}} +{c}^{\mathrm{2}} \right)=\left({a}+{b}+{c}\right)^{\mathrm{2}} −\mathrm{2}\left({ab}+{bc}+{ca}\right)=\mathrm{9}−\frac{\mathrm{18}}{\mathrm{7}} \\ $$$$=\frac{\mathrm{63}−\mathrm{18}}{\mathrm{7}}=\frac{\mathrm{45}}{\mathrm{7}} \\ $$$$\left({ab}\right)^{\mathrm{2}} +\left({bc}\right)^{\mathrm{2}} +\left({ca}\right)^{\mathrm{2}} =\left[{ab}+{bc}+{ca}\right]^{\mathrm{2}} −\mathrm{2}{abc}\left({a}+{b}+{c}\right) \\ $$$$=\frac{\mathrm{81}}{\mathrm{49}}+\frac{\mathrm{84}}{\mathrm{49}}=\frac{\mathrm{165}}{\mathrm{49}} \\ $$$$\Rightarrow{a}^{\mathrm{4}} +{b}^{\mathrm{4}} +{c}^{\mathrm{4}} =\left(\frac{\mathrm{45}}{\mathrm{7}}\right)^{\mathrm{2}} −\frac{\mathrm{330}}{\mathrm{49}}=\frac{\mathrm{1695}}{\mathrm{49}} \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com